2019
DOI: 10.1371/journal.pone.0211485
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and mechanical properties of the human triceps surae aponeuroses taken from elderly cadavers: Implications for muscle-tendon interactions

Abstract: The human triceps surae (two gastrocnemii and soleus) has aponeuroses in the proximal and distal aspects, the latter of which insert into the calcaneus by sharing the common Achilles tendon. These tendinous tissues are known to have elasticity and upon muscle contraction the aponeurosis is stretched both longitudinally (along the muscle’s line of action) and transversely. Higher aponeurosis transverse deformability has been documented, but there is a paucity of information on the morphology and mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…This result is consistent with a previous study which found that the Achilles tendon became stiffer after stretching [ 27 ]. Shan et al (2019) demonstrated that the stiffness of the medial head of the gastrocnemius and medial and lateral soleus was correlated with ankle joint position or muscle contraction [ 29 ]. Further, there was a significant increase in shear modulus of the medial head of the gastrocnemius and the lateral head of the gastrocnemius in the lengthened muscle position [ 26 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with a previous study which found that the Achilles tendon became stiffer after stretching [ 27 ]. Shan et al (2019) demonstrated that the stiffness of the medial head of the gastrocnemius and medial and lateral soleus was correlated with ankle joint position or muscle contraction [ 29 ]. Further, there was a significant increase in shear modulus of the medial head of the gastrocnemius and the lateral head of the gastrocnemius in the lengthened muscle position [ 26 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cases demonstrate the straining-stiffness behavior of muscles and tendons after the fibers become tight [ 31 ]. Many studies identified the stiffness of muscle in a tension state, but only a few studies focused on the change of tendon stiffness after stretching [ 29 , 30 ]. When the tendons and muscles respond to the same mechanical load, such as tension, they may have different stiffness modulation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is clear importance of the aponeurosis in musculoskeletal function, but there have been relatively few studies of aponeurosis material properties to date Bojsen-Møller and Magnusson, 2019;Shan et al, 2019). Determining the material properties of the aponeurosis will provide evidence of its structure and function to identify how it contributes to the movement of the musculoskeletal system.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lack of information reported in previous literature, damping coefficients (N×s/mm) were set to half the numerical value of stiffness (N/mm) in an effort to reduce high frequency oscillations at the contact interfaces, which can lead to rapidly-evolving ordinary differential equations and thus computational instability when simulating interface dynamics. (Zheng et al, 1999) 2 (Mak et al, 1994) 3 (Shan et al, 2019) The static coefficient of friction (µstatic) between the limb and socket was assigned a value of 0.5, based on an in vivo study of the interaction between silicon (a commonly used material for prosthetic socket liners) and the skin of the human leg (Zhang and Mak, 1999). Coefficients of friction between 0.5 and 3.0 have been reported for various other socket liner materials (Cagle, Hafner, Taflin, & Sanders, 2018; Joan E Sanders, Greve, Mitchell, & Zachariah, 1998).…”
Section: Model Parameterizationmentioning
confidence: 99%